Implementation of the AAMC's Holistic Review Model for Psychiatry Resident Recruitment - Robert Marvin; Yoon Soo Park; Michael Dekhtyar; Marla Hartzen; Laurel Bessey; Ryan Finkenbine; Brett Lloyd; Senada Bajmakovic-Kacila; Art Walaszek; Ara Tekian (Association of American Medical Colleges, 2023)
Introduction In psychiatry, several converging factors are impacting the recruitment of residents: the increased competitiveness of the specialty, the national trend to take active steps to improve diversity and inclusion, and the decision from USMLE to change Step 1 to a pass/fail result. Methods We developed a workshop for psychiatry residency program directors to meet these challenges and transition into using a holistic review model during recruitment. The workshop included (1) a didactic session providing background on the AAMC holistic review model; (2) a small-group exercise to determine and prioritize experiences, attributes, competencies, and metrics (EACMs) aligned with the program's mission and aims; (3) a review of the rankings from the previous exercise, selection of two "very important" criteria for each of the four domains of the EACM model, and operationalization of these criteria based on the recruitment process; and (4) a discussion focused on application of program criteria with example applicants. Results The holistic review workshop was conducted at the American Association of Psychiatry Residency Directors conference in 2021 with 48 self-selected attendees. Following the workshop, 74% of attendees reported a likelihood of implementing holistic applications during their next application cycle, 78% were able to leave with at least one actionable item, 100% thought that the session was interactive, and 78% felt that the session met their expectations. Discussion Implementing a holistic review for psychiatry residency recruitment can assist programs in responding to the rapidly changing landscape and achieve aims for improving diversity and inclusion.